Maximal Cartel Pricing and Leniency Programs - Harold Houba; Evgenia Motchenkova; Quan Wen (Tinbergen Institute, 2008)
For a general class of oligopoly models with price competition, we analyze the impact of ex-ante leniency programs in antitrust regulation on the endogenous maximal-sustainable cartel price. This impact depends upon industry characteristics including its cartel culture. Our analysis disentangles the effects of traditional antitrust regulation and the leniency program. Ex-ante leniency programs are effective if and only if these offer substantial rewards to the self-reporting firm. This is in contrast to currently employed programs that are therefore ineffective.
Keywords: L41; K21; C72; 330; Cartel; Antitrust Policy; Antitrust Law; Antitrust regulation; Leniency program; Self-reporting; repeated game; Kartell; Wettbewerbspolitik; Kartellrecht; Straffreiheit; Wiederholte Spiele; Nichtkooperatives Spiel; Theorie